Incidence of Retinal Complications in a Cohort of Newly Diagnosed Diabetic Patients - Martín-Merino, Elisa (Public Library of Science, 2014)
PURPOSE: We aimed at estimating the incidence of diabetic retinopathy (DR) and maculopathy (DMP) among newly diagnosed type 1 (t1DM) and type 2 diabetic patients (t2DM) in the United Kingdom primary care system. The incidence of DMP among patients with DR was also estimated. METHOD: We conducted a cohort study using The Health Improvement Network database. The cohort included 64,983 incident diabetic patients (97.3% were t2DM) aged 1–84 years diagnosed between 2000 and 2007. This cohort was followed from the date of diabetes diagnosis until recording of DR or DMP in two separate follow-ups. Follow-up was censored at 85 years of age, death, or end of 2008. An additional follow-up was conducted from DR to DMP diagnosis using similar censoring reasons. DR and DMP cumulative incidences were calculated as well as incidence rates (IR; cases per 1,000 person-years) per calendar period (2000–2001 and 2006–2007). RESULTS: Follow-up for DR: 9 years after diabetes diagnosis, 28% of t2DM and 24% of t1DM patients had developed DR (7,899 incident DR cases). During the first 2 years with diabetes, the IR was almost 2 times higher in patients diagnosed with diabetes in 2006–2007 (47.7) than among those diagnosed in 2000–2001 (24.5). Follow-up for DMP: 9 years after diabetes diagnosis, 3.6% of t2DM and 4.4% of t2DM patients had developed DMP (912 incident DMP cases). During the first 2 years with diabetes, the IR was three times higher in patients diagnosed with diabetes in 2006–2007 (5.8) than among those diagnosed in 2000–2001 (1.8). Macular oedema occurred in 0.8% of patients. CONCLUSIONS: In a cohort of incident diabetes, 28% of patients developed retinopathy and 4% maculopathy within the first 9 years. The 2-year IRs of DR and DMP were higher in patients diagnosed with diabetes during the period 2006–2007 than in those diagnosed during the 2000–2001 period.